2017
DOI: 10.1371/journal.pone.0180026
|View full text |Cite
|
Sign up to set email alerts
|

The SERTAD protein Taranis plays a role in Polycomb-mediated gene repression

Abstract: The Polycomb group (PcG) proteins have been implicated in epigenetic transcriptional repression in development, stem cell maintenance and in cancer. The chromodomain protein Polycomb (Pc) is a key member of the PcG. Pc binds to the histone mark, trimethylated histone 3 lysine 27 (H3K27me3), to initiate transcriptional repression. How PcG proteins are recruited to target loci is not fully understood. Here we show that the Drosophila SERTA domain protein Taranis (Tara) is involved in transcriptional regulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…Clones expressing both tara and ban did not have an obvious decrease in En expression ( Fig. 3E′), although a reduction in tara has previously been linked to result in increased En expression (34,35). Thus, tara likely regulates ci expression independently of en.…”
Section: Resultsmentioning
confidence: 84%
“…Clones expressing both tara and ban did not have an obvious decrease in En expression ( Fig. 3E′), although a reduction in tara has previously been linked to result in increased En expression (34,35). Thus, tara likely regulates ci expression independently of en.…”
Section: Resultsmentioning
confidence: 84%
“…To understand the role of tara in the testis niche, we knocked down tara in the niche using a UAS‐taraRNA i transgene construct that produces dsRNA against tara . As we have previously shown, this UAS‐tara RNA i transgene, when driven by a Tubulin‐Gal4 , results in a 90% reduction in endogenous tara transcripts without affecting Pc levels 19 . We thus took advantage of the UAS‐tara RNA i transgene to knockdown tara in different cell types with different Gal4 lines.…”
Section: Resultsmentioning
confidence: 99%
“…However, neither Nos‐Gal4 > UAS‐taraRNAi nor Upd‐Gal4 > UAS‐taraRNAi showed any appreciable GSC loss phenotype (Figure 3A,B). We also employed the Flp‐FRT technique to create germline clones homozygous for tara loss‐of‐function allele tara 03881 19 . We observed that, multiple tara null GSCs (marked by loss of GFP; N = 21/32 testes) survived even after 10 days post clone induction, comparable to wild‐type control GSCs (N = 19/34 testes) (Figure 3C; Table S2), in agreement with the tara RNAi experiment carried out with the germline Nos‐Gal4 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations